Influence of structural capacity uncertainty on seismic reliability of buildings under narrow-band motions. - Montiel, M. A.
The influence of parameter uncertainties on the seismic reliability of several structural reinforced concrete buildings is analysed. Drift hazard curves of buildings considering mean values of their material properties and of instantaneous live loads are compared with those considering uncertain values. Influence of uncertainty in the storey drift capacity and, alternatively, in intensity capacity on the structural annual failure rates is evaluated. The structural capacity is estimated by incremental dynamic analysis (IDA). It is shown that for the analysis of structures that ?soften? into a peak of their corresponding spectra associated with narrow-band motions it could be more adequate to use the peak storey drift as a measure of structural capacity, rather than the intensity that causes the failure. The study makes emphasis on the importance of the acceleration spectral shape on the reliability of structures.
Keywords: Structural reliability; Structural ?softening?.; Narrow-band motions; Uncertainty in structural capacity; Failure intensity